2014
DOI: 10.1007/s00592-014-0597-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of duration and dose of metformin on cobalamin deficiency in type 2 diabetes patients using metformin

Abstract: Metformin use is associated with cobalamin (vitamin B12) deficiency. However, the influence of both duration and dose of metformin is unclear. Studies using holotranscobalamin, a marker for cellular cobalamin deficiency, are scarce. We therefore investigated the prevalence of cobalamin deficiency in type 2 diabetes patients using both markers, and its relation with duration and dose of metformin use. This cross-sectional study among 550 type 2 diabetes patients using metformin (mean daily dose 1,306 mg; mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 31 publications
7
62
0
4
Order By: Relevance
“…This suggests that at least part of the association between metformin and anemia is through reduced serum vitamin B 12 , although deficiency of the active form (holotranscobalamin) occurs in b 4% of metformin-treated patients. 36 There have been rare cases of metformin-associated acute hemolysis 37 but chronic low-grade hemolysis has not been reported. Metformin can lower serum magnesium concentrations, 38 and there is evidence of an inverse association between hypomagnesemia and anemia which might be explained by the requirement for magnesium as an essential cofactor for enzymes involved in hemoglobin synthesis and erythrocyte metabolism and/or the association between hypomagnesemia and oxidative stress, inflammation and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that at least part of the association between metformin and anemia is through reduced serum vitamin B 12 , although deficiency of the active form (holotranscobalamin) occurs in b 4% of metformin-treated patients. 36 There have been rare cases of metformin-associated acute hemolysis 37 but chronic low-grade hemolysis has not been reported. Metformin can lower serum magnesium concentrations, 38 and there is evidence of an inverse association between hypomagnesemia and anemia which might be explained by the requirement for magnesium as an essential cofactor for enzymes involved in hemoglobin synthesis and erythrocyte metabolism and/or the association between hypomagnesemia and oxidative stress, inflammation and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…All of these studies have supported a reduction in B12 status with metformin use, or higher than expected levels of deficiency in metformin using patients. Of note, Beulens et al (2015) found both reduced vitamin B12 and holotranscobalamin in metformin users [51]. Therefore, inclusion of these articles would have been unlikely to change the overall results of our systematic review, although it is important to note that the study by de Groot- Kamphuis et al (2013) found that metformin use was not associated with risk of neuropathy or anaemia [46].…”
Section: Discussionmentioning
confidence: 98%
“…The concordance with the other meta-analysis also supports the reliability of our effect size. Since our electronic searches were completed there have been 8 observational studies published that are relevant to our review [45][46][47][48][49][50][51]. All of these studies have supported a reduction in B12 status with metformin use, or higher than expected levels of deficiency in metformin using patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between metformin use and low vitamin B12 was described in many observational studies (11,12,(15)(16)(17)20,90). Randomized clinical trials have proved that receiving the medication for a few months can significantly lower vitamin B12 levels (91)(92)(93).…”
Section: The Effect Of Metformin On Vitamin B12 Levelsmentioning
confidence: 99%
“…Several aspects of the topic, however, still await clarifications. The reported prevalence of vitamin B12 deficiency among metformin-treated patients has shown great variation and ranged between 5.8% and 52% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). A substantial part of the problem is the yet incompletely defined term of vitamin B12 deficiency.…”
Section: Introductionmentioning
confidence: 99%